2010
DOI: 10.1080/15459621003729966
|View full text |Cite
|
Sign up to set email alerts
|

Personal Exposure of Traffic Police Officers to Particulate Matter, Carbon Monoxide, and Benzene in the City of Milan, Italy

Abstract: The aim of this work was to quantify the personal exposure of traffic police officers to particulate matter (PM), carbon monoxide (CO), benzene, toluene, ethylbenzene, and xylenes. The contributions of some behavioral, occupational, and meteorological determinants of exposure also were evaluated. Personal exposure to airborne contaminants was measured on 130 selected volunteers in four seasonal sampling sessions. CO was measured with high sampling frequency. A time-activity diary was completed by traffic polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 52 publications
(77 reference statements)
3
20
1
Order By: Relevance
“…The exposure of traffic police officers to particulate matter, carbon monoxide, and benzene has been assessed. The key finding was that airborne concentrations determined by a fixed measurement reported in other studies greatly underestimated the exposure of traffic officers to airborne contaminants [87]. pollution and its carcinogenic effect on the exposed individuals.…”
Section: Other Studiesmentioning
confidence: 90%
“…The exposure of traffic police officers to particulate matter, carbon monoxide, and benzene has been assessed. The key finding was that airborne concentrations determined by a fixed measurement reported in other studies greatly underestimated the exposure of traffic officers to airborne contaminants [87]. pollution and its carcinogenic effect on the exposed individuals.…”
Section: Other Studiesmentioning
confidence: 90%
“…Studies in literature show that traffic policewomen are daily exposed to chemical urban pollutants (Tomei et al 2004;Maffei et al 2005;Cattaneo et al 2010) and in previous research we have observed effects of exposure to urban stressor on plasma follicle stimulating hormone (FSH) in a group of male traffic policemen (Tomei et al 2009). The gonadotropin FSH is synthesized and secreted by gonadotrope cells of the anterior pituitary gland.…”
Section: Introductionmentioning
confidence: 91%
“…The flow rate of the sampling pumps was controlled and calibrated immediately before and after sampling using a certified rotameter. 10 A sampling plastic tube was connected with an inlet port and placed at a height that was at the same height of breathing, so that it would represent the individual's actual exposure. The duration was from 8:00 AM of 1 day to 8:00 AM of the next day.…”
Section: Individual Exposure Assessmentmentioning
confidence: 99%